Cancer and sexual health - Mulhall, John P.; Incrocci, Luca 1962-; Goldstein, Irwin; Rosen, Ray 1946- (Current clinical urology., 2011)
The average physician and even cancer care-givers are not knowledgeable about the effects of cancer treatment on sex and reproductive life. They are even less aware of the options available for treatment of such patients. Cancer and Sexual Health fills a great need for a reference work devoted to the link between cancer and human sexuality. The volume is designed to give a comprehensive and state-of-the-art review of the sexual and reproductive consequences of cancer diagnosis and treatment. It will prove an invaluable resource for those clinicians caring for cancer patients as well as acting as a reference text for the sexual medicine clinician who may not see a large number of cancer patients.